Pengaruh Pengelolaan Barang Milik Daerah Terhadap Kualitas Laporan Keuangan Pemerintah Kabupaten Aceh Barat - Putri Usiyani; Linda Rahmazaniati (Jurnal Ekonomika dan Bisnis, 2022)
In analyzing the quality of financial reports on the influence of the management of Regional Property of the West Aceh Regency Government. The sampling method used primary data, the sample taken amounted to 35 respondents, using quantitative research analysis. From the test results using SPSS 25 software, namely using a simple linear regression analysis test. The results showed that the management of Regional Property had a significant effect on the financial statements, and the variable of the management of Regional Property had an effect on the variable of the quality of the financial statements. This means that the management of regional property has a positive effect on the quality of the Aceh Government's financial reports.